Knock out hepatic Krüppel-like factor 16 (KLF16) improve myocardial damage and promoted myocardial protection of myocardial ischemia-reperfusion via anti-oxidative and anti-inflammation effects by TFAM/PPARβ signal passage. Issue 2 (20th December 2021) - Xin, Yue; Su, Pixiong; Liu, Yan; Gu, Song; an, Xiangguang; Zhang, Xitao; Yan, Jun; Guo, Yulin; Zhou, Jian; Yang, Guilin
ABSTRACT: This study is aimed at investigating mechanisms and effects of Krüppel-like factor 16 (KLF16) affects myocardial ischemia-reperfusion. Patients with myocardial ischemia-reperfusion and normal volunteer were collected. C57BL6J male mice were located left anterior descending coronary artery (LAD). H9c2 cell was induced with hydrogen peroxide (H2O2) and Lipopolysaccharide (LPS). Serum KLF16 mRNA expression was increased in myocardial ischemia-reperfusion. Serum mRNA of KLF16 was positive correlation with serum creatine kinase MB (CK-MB) or creatine kinase (CK) levels in patients with myocardial ischemia-reperfusion. The expression of KLF16 mRNA and protein in mice with myocardial ischemia-reperfusion were also increased. The inhibition of KLF16 reduced oxidative stress and inflammation, and presented myocardial ischemia (MI) in vivo model of myocardial ischemia-reperfusion. Mitochondrial transcription factor A (TFAM )/peroxisome proliferator-activated receptor-beta (PPARβ) signal passage is target spot of KLF16 in Myocardial ischemia-reperfusion. TFAM interlink KLF16 in myocardial ischemia-reperfusion. TFAM participate in KLF16 affects myocardial ischemia-reperfusion. PPARβ promoter region KLF16 affects myocardial ischemia-reperfusion. These results firstly demonstrated that knock-out KLF16 reduced oxidative stress and inflammation, and presented MI in vivo model of myocardial ischemia-reperfusion through the induction of PPARβ by TFAM, may provide a novel therapeutic strategy for myocardial ischemia-reperfusion.